SIKAP MASYARAKAT TERHADAP ARUS INFORMASI DI MASA PANDEMI COVID 19: KEGIATAN PENYULUHAN KEPADA PERSATUAN WANITA DARUSSALAM (PWD) - Erna Kumalasari Nurnawati; Ellyawan Setyo Arbintarso (Universitas PGRI Yogyakarta, 2021)
The Covid19 pandemic that has hit the entire world since March 2020 provides various aspects of people's lives: economic, social, behavior, and life habits. One aspect that often occurs is the flood of information about a pandemic, especially in the early days of the virus outbreak. This community service aims to provide understanding in responding to the flood of information during the pandemic to the public, especially the women at the Persatuan Wanita Darussalam (PWD) in Darussalam 3 Residential, Ngemplak, Sleman. The method used in community service is by observing the subject, providing online counseling using the zoom meeting application by utilizing the RT / RW Net in the housing and followed by follow-up monitoring in the form of post-extension monitoring. The result of this service activity is that the community, especially, gets learning and understanding how to deal with the flood of information during the pandemic, especially in filtering real and false information (hoax).